Multidisciplinary Mentoring Programs to Enhance Junior Faculty Research Grant Success. (October 2017) - Freel, Stephanie A.; Smith, Paige C.; Burns, Ebony N.; Downer, Joanna B.; Brown, Ann J.; Dewhirst, Mark W.
Abstract : Problem: Junior faculty face challenges in establishing independent research careers. Declining funding combined with a shift to multidisciplinary, collaborative science necessitates new mentorship models and enhanced institutional support. Approach: Two multidisciplinary mentorship programs to promote grant success for junior faculty were established at the Duke University School of Medicine beginning in 2011. These four-month programs—the Path to Independence Program (PtIP) for National Institutes of Health (NIH) R applicants and the K Club for NIH K applicants—use multiple senior faculty mentors and professional grant-writing staff to provide a 20-hour joint curriculum comprising a series of lectures, hands-on workshops, career development counseling, peer groups, and an internal study section. In March 2016, the authors analyzed the success rate for all NIH grants submitted by participants since program enrollment. In a 2015 postprogram survey, participants rated their feelings of support and competency across six skill factors. Outcomes: From October 2011 to March 2016, the programs engaged 265 senior faculty mentors, 145 PtIP participants, and 138 K Club participants. Success rates for NIH grant applications were 28% (61 awards/220 decisions) for PtIP participants—an increase over the 2010 Duke University junior faculty baseline of 11%—and 64% (38/59) for K Club participants. Respondents reported significantly increased feelings of support and self-ratings for each competency post program. Next Steps: The authors plan to expand the breadth of both the mentorship pool and faculty served. Broad implementation of similar programs elsewhere could bolster success, satisfaction, and retention of junior faculty investigators. Abstract : Supplemental Digital Content is available in the text.